True-3D in cartography : autosteroscopic and steric visualisation of geodata - Buchroithner, Manfred F. (Lecture notes in geoinformation and cartography, 2012)
This book assesses the current state of True 3D support in cartography and GI Systems. It focuses on visualization modules of GI software and systems, and addresses the specific question "How commonly is stereoscopic visualization supported in GI systems?"